Cytoprotective effects of curcumin on the state of the intestinal barrier in a model of LPS-induced inflammation - V. S. Nedzvetsky; O. V. Yanovska; D. F. Gufrij; O. A. Sheptukha; D. M. Masiuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Intestinal epithelium forms tissue barrier to prevent infectious agents invasion as well as provides interaction between external environment and internal body compartment. Intestinal barrier is functioning is susceptible to inflammatory complications. Barrier integrity requires physical intercellular adhesion of epithelial cells via tight junction proteins links. The interrelation between intestinal inflammation and barrier integrity was the aim of present study. The Caco-2 cell culture was exposed to lipopolysaccharide (LPS), curcumin and LPS+curcumin to assess the effect of this polyphenol on the intestinal barrier. Cell viability, TNF-α, and occludin contents were detected in cell lysates after 48 hours exposure. Obtained results demonstrated that LPS induced TNF-α upregulation and decrease in cell viability and occluding in dose-dependent manner. The treatment with curcumin didn’t affected any studied parameters. Contrary, curcumin exposure ameliorates cell viability and occludin content in LPS-challenged cells. Therefore, the effect of curcumin on inflammatory provoked cells and normal balanced cells is differentiated in respect to cell proinflammatory reactivity. Furthermore, the protective effect of curcumin is associated with maintenance of LPS-compromised intestinal barrier. Obtained results evidence that soluble curcumin is a promised tool to protect the main intestinal functions including barrier integrity.